The precariousness of Peruvian public employment - Canessa Montejo, Miguel F. (2022)
The political debate emphasises the tasks that the state must fulfil in the face of the health and economic crisis, without assessing whether the public servants who work in the state have the capacities and skills to face these tasks. It is assumed that the Peruvian state can implement public policies based on improvisation. This is evidence of a real lack of knowledge about the working conditions of public employment. In turn, labour lawyers reduce the analysis to the exegesis of the regulation and the compilation of judicial sentences or resolutions of the National Civil Service Authority (Servir), without linking the regulation and the statistics that measure the indicators of public employment, so that we leave this connection aside or even reduce the normative proposals to a mere legal abstraction without any correspondence with the reality and its consequences that affect public servants. This article analyses public labour regimes and the impact of their application on the structure of public employment, linking the description of the regulation and the statistical results, presenting a socio-legal panorama of Peruvian public employment.